Anti Bacterial Activity of Cabbage Extract - saleh, Dina suhail m; Majeed, Mohammed Fawzi; alazeez, Enas Kasim abd; Khalaf, Sarah Hussain (American Journal of Biomedicine and Pharmacy, 2025)
In recent years discovered that medicinal plant used as anti-bacterial agent . the adverse effect of chemical synthesis of anti-bacterial drugs increase the chance for use therapeutic plants as source of anti-bacterial therapy . This study aimed to evaluate anti-bacterial activity of Cabbage by analyze the photochemical component of this fruit .In this study Alcoholic extract of Cabbage leaves were used for antibacterial activity against various lactic acid bacteria Gram-Positive and Gram Negative bacteria ( Pseudomonas aeruginosa , E coli , Staphylococcus aureus , Staphylococcus epidermidis and Streptococcus pyogens ) by using disc diffusion method .The result showed that the Alcoholic extract of Cabbage have antibacterial activity and inhibit the growth of all tested bacteria . The G-Positive bacteria were more sensitive to the extract than the G-Negative bacteria , the zone of inhibition of staphylococcus aureus was ( 12mm ) while the inhibition zone of E-coli was ( 1Omm ) .